Effect of Bcl-2 Expression on Hybridoma Cell Growth in Serum-Supplemented, Protein-Free and Diluted Media - Fassnacht, D. (Kluwer Academic Publishers, 1998)
Two transfected hybridoma cell lines TB/C3-bcl2 (overexpressing the Bcl-2 protein) and TB/C3-pEF (control cell line), were compared in batch suspension cultures using a medium supplemented either with horse serum or with a protein-free, iron-rich supplement. The membrane intact index (percentage of cells with intact membranes determined by trypan blue staining) of the TB/C3-bcl2 cell line decreased much slower than that of the control cell line during the dying phase of the cultures. No significant difference in antibody, lactate and ammonia production as well as glucose and glutamine consumption was noted in the exponential phase of the experiments. Both cell lines were also compared in batch experiments using media diluted with saline to further investigate the effect of Bcl-2 under sub-optimal conditions. The Bcl-2 overexpressing cell line again exhibited a higher membrane intact index at increasing dilution steps.